THE INTEGRATION OF EDUCATIONAL GAMES IN MATHEMATICS LEARNING AT PRIMARY SCHOOLS - Airich Angel Mahinay (SMART: Journal of Multidisciplinary Educational, 2025)
This study aims to explore and compare the effectiveness of digital and non-digital educational games in enhancing primary school students' mathematics learning outcomes. Employing a literature review method, the research systematically examines peer-reviewed studies from the past five years to identify trends, gaps, and implications in the integration of game-based learning (GBL) in primary mathematics instruction. The analysis focuses on several key variables including game format, curriculum alignment, teacher readiness, student motivation, and retention of mathematical understanding. The findings indicate that while both digital and non-digital games have positive impacts, non-digital games tend to produce higher effect sizes, especially in resource-limited classroom contexts. The study also reveals that successful implementation is influenced by factors such as game design quality, pedagogical integration, and the teacher’s role in facilitating learning. This research presents novelty by offering a comparative analysis of game formats, examining medium-term learning retention, and situating the discussion within an under-researched cultural context—Indonesian primary education. Furthermore, it considers how individual learner characteristics and instructional design features interact to influence outcomes. The study concludes that game-based learning in mathematics is most effective when implemented systematically, aligned with curriculum objectives, and supported by well-prepared educators. These findings contribute practical insights for educators, policymakers, and curriculum developers globally, especially those seeking to adapt game-based strategies within diverse and resource-constrained settings. Future research is encouraged to apply longitudinal and mixed-method designs to further validate the long-term impact of educational games in mathematics learning environments.